Student Perceptions Of The Islamic Broadcasting Communication Study Program (Case Study Of FDIK IAIN Padangsidimpuan) - Nurfitriani M. Siregar (Hikmah, 2021)
This study discusses the perception of students choosing the Islamic communication and broadcasting study program at the Faculty of Da'wah and Communication Sciences IAIN Padangsidimpuan. This research is descriptive in nature, that is, this research was conducted to determine the value of independent variables, either one or more (independent) variables without making comparisons, or connecting with other variables, then the approach used in this study was a qualitative approach. Student perceptions in choosing KPI study programs FDIK IAIN Padangsidimpuan is in the good category. And also there are things that need to be improved the quality of the infrastructure that supports the facilities in the learning process at the KPI FDIK IAIN Padangsidimpuan study program.